Languaging, Corrective Feedback, and Writing Accuracy among Low Proficiency L2 Learners - Abd Rahim, Sabariah; Jaganathan, Paramaswari (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2022)
Low proficiency L2 learners make frequent grammatical errors and apply inappropriate English language use and writing conventions despite learning the language for years. To reduce the grammatical and non-grammatical errors in the low proficiency L2 learners’ writing, teachers provide Written Corrective Feedback (WCF). However, a strong claim on WCF's adverse effects on L2 learners’ language development has prompted mixed responses on the WCF’s effectiveness. Numerous studies on WCF's effectiveness were conducted, and the findings showed inconclusive results. The present study aims to examine the ‘Written Languaging’ (WL) effect of Written Corrective Feedback (WCF) on low proficiency L2 learners’ writing accuracy. WL is a mediational tool used to enhance the WCF’s effectiveness. The study was conducted on 47 low proficiency L2 university students for five weeks to elicit WL of WCF's effects on low proficiency L2 learners’ writing accuracy, where a multiple-case research approach was used to collect and analyze the data of the study. An error ratio was applied to measure the overall accuracy of writing. The Wilcoxon signed-rank test was used to determine whether WL's provision on the WCF affects the writing accuracy of the low proficiency L2 learners' new writing text. The finding shows that WL's provision on the WCF did not facilitate the low proficiency of L2 learners' writing accuracy because the L2 learners' writing accuracy could improve only with teachers' WCF. The study is significant to the pedagogical teaching of writing development for lower proficiency L2 learners, particularly in applying the mediational tool in the provision and processing of WCF and the complementary pedagogical strategy to WCF.